Development of Online Web “Ayo Dolanan” as a Media for Preserving Traditional Games For Gen Z in Semarang City - Javier, Mochammad Alban; Wahyudi, Agung (Universitas Majalengka, 2024)
Technology development has greatly affected the fading of traditional games in people's lives. Especially with the existence of modern games that are increasingly sophisticated and interesting, traditional games lose prestige. The research aims to develop a traditional game preservation media in the form of online media, which was originally a threat, to be used as a preservation media with the creation of this